Monitoring of indoor bioaerosol for the detection of SARS-CoV-2 in different hospital settings - Tedeschini, Emma; Pasqualini, Stefania; Emiliani, Carla; Marini, Ettore; Valecchi, Alessandro; Laoreti, Chiara; Ministrini, Stefano; Camilloni, Barbara; Castronari, Roberto; Patoia, Lucio; Merante, Francesco; Baglioni, Stefano; et al. (Frontiers in Public Health, 2023)
Background: Spore Trap is an environmental detection technology, already used in the field of allergology to monitor the presence and composition of potentially inspirable airborne micronic bioparticulate. This device is potentially suitable for environmental monitoring of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in hospital, as well as in other high-risk closed environments. The aim of the present study is to investigate the accuracy of the Spore Trap system in detecting SARS-CoV-2 in indoor bioaerosol of hospital rooms. Methods: The Spore Trap was placed in hospital rooms hosting patients with documented SARS-CoV-2 infection (n= 36) or, as a negative control, in rooms where patients with documented negativity to a Real-Time Polymerase Chain Reaction molecular test for SARS-CoV-2 were admitted (n=10). The monitoring of the bioaerosol was carried on for 24 hours. Collected samples were analysed by real-time polymerase chain reaction. Results: the estimated sensitivity of the Spore Trap device for detecting SARS-CoV-2 in an indoor environment is 69.4% (95% C.I. 54.3-84.4%), with a specificity of 100%. Conclusion: The Spore Trap technology is effective in detecting airborne SARS-CoV-2 virus with excellent specificity and high sensitivity, when compared to previous reports. The SARS-CoV-2 pandemic scenario has suggested that indoor air quality control will be a priority in future public health management and will certainly need to include an environmental bio-investigation protocol.